The Design and Implementation of Blended Learning Teaching Grammar for English Education Students - Safwan, Renita Maeta; Sujana, I Made; Farmasari, Santi; Waluyo, Untung (Jurnal Ilmiah Profesi Pendidikan, 2023)
Teaching grammar was considered very important to the ability to use language. Learning more about grammar will help students produce better sentences while speaking and writing. For this reason, this article introduces different ways of teaching grammar. This research aimed to analyze the design and implementation of Blended Learning in Basic English Grammar classes. This research used mixed methods. The subject in this research was the students from the 1st semester English department of the University of Mataram and the lecturer who taught Basic English Grammar using Blended Learning. The data were collected through observation, questionnaire, interview, and documentation. The results of this study showed that the design of Blended Learning using ICARE as a model of learning in Basic English Grammar for 1st-semester students is great. The students give positive and negative responses toward the use of blended learning. Furthermore, the student’s achievement in Basic English Grammar showed a positive impact. Where the student’s average score on the mid-test was (67.36%). While on the final test was (75.49%). To sum up, implementing blended learning is successful and positively impacts student’s achievement in Basic English Grammar.